The Role of Metallic Connections in the Global Behavior of Timber Frame Structural System of Tabique Walls - José Padrão (2021)
In order to perform a correct and efficient rehabilitation of old building, it is required to know the materials used, their main properties as well as the construction process. Tabique Walls (TW) are primary building components of many constructions in the historic center of Viseu and their function, in addition to being used as partitioning elements (the most common in Portugal), is to be part of the main structure of buildings. In this sense it is essential to understand how the TW interconnect with each other and with the other main structural elements of buildings, namely the floors and the stone masonry walls. The important role of metallic connectors in the realization of these bonds is emphasized. This paper presents the research carried out in several buildings of the historic center of Viseu. Several constructive solutions found are detailed, associating the shapes and dimensions of the connectors to their function, and results are presented out of a primary campaign of laboratory tests carried out to define their mechanical properties. The knowledge obtained allows a better understanding of the overall structural behavior of these buildings and the role of the TW in that behavior.